Directed but reflecting: Guided team reflexivity as an intervention to foster team performance improvement under directive leadership - Santos, C. M.; Uitdewilligen, S.; van der Vegt, L.; Schippers, M. C.; Passos, A. M. (Group and Organization Management, 2026)
Guided reflexivity interventions (i.e., formal and structured interventions to induce teams to engage in team reflexivity) have been touted as being beneficial in terms of team processes and team performance. However, it is less well known under what conditions a guided team reflexivity intervention is beneficial for team performance improvement. Importantly, the leadership style employed by the team leader, i.e. directive versus empowering, may determine under what conditions guided team reflexivity is more beneficial for team performance over time. Drawing on the motivated information processing in groups (MIP-G) theory and on reflexivity theory, we argue that a guided team reflexivity intervention is particularly helpful for teams with directive leaders because those leaders do not foster team reflexivity. To test this, we conducted two experimental studies manipulating leadership style (directive vs empowering) and guided team reflexivity (reflexivity vs no-reflexivity). In Study 1, 37 three-person teams composed of aspirant army officers performed the Virtual Battle Space simulation. In Study 2, 77 three-person teams composed of undergraduate students performed an emergency management simulation. Random coefficient modelling was used to test the hypotheses. Across both studies, and in line with our hypotheses, we found that the positive effect of guided team reflexivity on team performance improvement is higher in teams with directive leaders than in teams with empowering leaders. Thus, we found support for the idea that teams led by directive leaders benefit from guided team reflexivity for improving performance over time.